SURVEI KONDISI FISIK DAN KETERAMPILAN TEKNIK DASAR BOLA VOLI PADA ANAK USIA DINI (9-11) TAHUN DI KLUB BOLA VOLI PUTRI WAHANA UTAMA PURWODADI TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2015)
Study aimed to determine the physical condition of the basic techniques and skills of volleyball in children aged ( 9-11 ) years in club Wahana Utama volleyball daughter. This research is descriptive quantitative approach. The sampling technique used was purposive sampling. The method used in this study is a survey of testing techniques and methods of data analysis using descriptive data analysis. Based on the survey results revealed that the physical condition of children aged ( 9-11 ) years in women's volleyball club Wahana Utama Purwodadi 15 % is included in the category of less, 60 % are moderate and 25 % is included in both categories. The level of ability of the basic techniques of volleyball in early childhood ( 9-11 ) years in women's volleyball club Wahana Utama Purwodadi for passing over 100 % in both categories once , passing under the category of either 20 %, 80 % very well, 35 % in service less category, 65 % medium category, smashes 15 % in the category of less, 25 % moderate category, 25 % good category, 35 % in both categories once. The conclusions of the study is the physical condition of the average child in the criteria being the basic techniques and skills in the poor category.